Kinetics of color change of osmotically dehydrated chub mackerel (Scomber japonicus) during storage at different temperatures - CHECMAREV,Gerardo (2017)
Abstract The aim of this study was to determine the effect of storage temperature on the kinetics of color change of chub mackerel dehydrated in a ternary solution (water, glycerol and salt) and vacuum packaged in films. The color of processed fish can change because of lipids and protein oxidation during storage. Samples were stored at 7, 25 and 35 °C for seven months and kinetic models of 0, 1 and 2 order were applied to describe the color changes. It was observed that an increase in the storage temperature improved the changes in the CIE color values (L*, a* and b*). First-order reaction had the best statistical parameters for a* at the three temperatures tested. The temperature dependence of parameter a* indicated an Arrhenius relationship and the activation energy (Ea) was 44.33 kJ/mol. The parameter b* fitted to the proposed models only in samples stored at 35 °C. The L* value decreased during storage at 25 and 35 °C (pale to dark). Storage at refrigeration temperature (7 °C) minimized the color changes.